Diversity and abundance of antibiotic resistance genes and their relationship with nutrients and land use of the inflow rivers of Taihu Lake - Fernanda, Prilli Arista; Liu, Shuang; Yuan, Tianma; Ramalingam, Bharathi; Lu, Jing; Sekar, Raju (Frontiers in Microbiology, 2022)
Taihu Lake is the third largest freshwater lake in China and an important source for drinking water, flood protection, aquaculture, agriculture and other activities. This lake is connected to many principal and small rivers with inflow from west and outflow on the eastern side of the lake and these inflow rivers are believed to significantly contribute to the water pollution of the lake. This study was aimed at assessing the diversity and abundance of antibiotic resistant genes (ARGs) and mobile genetic elements (MGEs), and their relationship with water quality parameters and land use patterns. Water samples were collected from 10 major inflow rivers and the source water protection area of the Taihu lake in spring and summer 2019. High-throughput profiling was used to detect and quantify 384 ARGs and in addition, 11 water quality parameters were analyzed. The results showed that the number of ARGs detected in each inflow river ranged from 105 to 185 in spring and 108 to 180 in summer. The genes resistant to aminoglycoside was the most dominant types of ARGs detected, followed by beta-lactamase, multi-drug resistant (MDR), macrolids-lincosamides-steptogramin B (MLSB), which contributed to >54% of the total ARGs. The water quality parameters showed significant correlation with absolute abundance of ARGs. Furthermore, significant correlation between ARGs and MEGs were also observed which demonstrates that the potential gene transfer among organisms through horizontal gene transfer via MGEs. ARGs showed strong positive correlation with cultivated land and industrial land whereas, negative correlation was observed with river, lake, forest, land for green buffer, and land for port and harbour. The overall results indicate that the inflow rivers of Taihu lake are polluted by various sources including multiple nutrients and high abundance of ARGs, which needs attention for better management of the inflow rivers of this lake.